ナンキョク ショウワキチ ニ オケル セイジョウ タイキ カンソクシツ ノ セッチ ニツイテ - 長田, 和雄; オサダ, カズオ; 林, 政彦; ハヤシ, マサヒコ; 塩原, 匡貴; シオバラ, マサタカ; 原, 圭一郎; ハラ, ケイイチロウ; 和田, 誠; ワダ, マコト; 橋田, 元; ハシダ, ゲン; et al. (情報・システム研究機構国立極地研究所, 2006)
P(論文) 南極大気のモニタリング観測およびプロジェクト研究観測に資するため,南極・昭和基地に19m^2の清浄大気観測室(通称エアロゾル観測小屋)を設置した.第45次日本南極地域観測隊の夏季作業で,昭和基地の主要部から約300m風上に建設し,2004年2月10日から大気エアロゾルとオゾンの連続観測を開始した.この観測室は電気暖房と外気の取り込みで室温を約20°C に保つようになっている.6m高の観測タワーとエアロゾル観測用の試料大気導入管も有している.この報告では,設置に至る背景から観測室の詳細と初年度から2年度の運用状況と問題点,導入管の特性などについて述べる.運用初年度は,基地主要部に位置する観測棟で従来から行っているエアロゾル濃度やオゾン濃度のモニタリングと並行して観測を行った.双方の観測値を比較したところ,観測棟における従来の状況に比べて,清浄大気を観測した有効率は最大で1割ほど向上したことがわかった. An observatory (19m^2 inside area) was built for monitoring clean air constituents, such as aerosol particles and ozone, near the core block of Syowa Station. The observatory is located about 300m windward of the main buildings of Syowa Station to reduce atmospheric contamination from an electric power plant and other station activities. Continuous observations of aerosols and surface ozone started on February 10, 2004. The observatory uses electric heaters and outside cool air to control room temperature at about 20°C ±3°C to avoid self contamination by heating fuel combustion. The observatory has a 6-m height tower for an air inlet system that connects to an aerosol sub-sampling line under constant laminar air flow condition. Comparison of aerosol data between the Kansokutou (Atmospheric Observatory in the main station area) and this new observatory from February 2004 to January 2005 suggests that the effectiveness for monitoring clean air was improved about 10%. departmental bulletin paper